Case Report of a Massive Thigh Hematoma after Adductor Canal Block in a Morbidly Obese Woman Anticoagulated with Apixaban - Katherine L. Koniuch; Bradley Harris; Michael J. Buys; Adam W. Meier (Case Reports in Anesthesiology)
Hematoma formation after peripheral nerve block placement is a rare event. We report a case of a morbidly obese patient who was anticoagulated with apixaban and developed a massive thigh hematoma after an ultrasound-guided adductor canal block. Despite continuous visualization of the block needle, an unrecognized vascular injury occurred leading to a 14-cm hematoma in the anterolateral thigh. Morbid obesity warrants additional risk consideration when placing nerve blocks in an anticoagulated patient. In addition, early recognition and expert consultation are both important in the management of block-related hematomas.